The Transcriptional Regulator TFB-RF1 Activates Transcription of a Putative ABC Transporter in Pyrococcus furiosus - Reichelt, Robert; Ruperti, Katharina M. A.; Kreuzer, Martina; Dexl, Stefan; Thomm, Michael; Hausner, Winfried (Frontiers in Microbiology, 2018)
Transcription factor B recruiting factor 1 (TFB-RF1; PF1088) is a transcription regulator which activates transcription on archaeal promoters containing weak TFB recognition elements (BRE) by recruiting TFB to the promoter. The mechanism of activation is described in detail, but nothing is known about the biological function of this protein in Pyrococcus furiosus. The protein is located in an operon structure together with the hypothetical gene pf1089 and western blot as well as end-point RT-PCR experiments revealed an extremely low expression rate of both proteins. Furthermore, conditions to induce the expression of the operon are not known. By introducing an additional copy of tfb-RF1 using a Pyrococcus shuttle vector we could circumvent the lacking expression of both proteins under standard growth conditions as indicated by western blot as well as end-point RT-PCR experiments. A ChIP-seq experiment revealed an additional binding site of TFB-RF1 in the upstream region of the pf1011/1012 operon, beside the expected target of the pf1089/tfb-RF1 region. This operon codes for a putative ABC transporter which is most-related to a multidrug export system and in vitro analysis using gel shift assays, DNase I footprinting and in vitro transcription confirmed the activator function of TFB-RF1 on the corresponding promoter. These findings are also in agreement with in vivo data, as RT-qPCR experiments also indicate transcriptional activation of both operons. Taken together, the overexpression strategy of tfb-RF1 enabled the identification of an additional operon of the TFB-RF1 regulon which indicates a transport-related function and provides a promising starting position to decipher the physiological function of the TFB-RF1 gene regulatory network in Pyrococcus furiosus.